Elaboracion de un sistema de produccion ovina para la precordillera de Bio-Bio - Klee G, G.=700 1 Crempien C, C.; Acuña P, H.; Fernandez R, M.
(ES, En)
Ilus., 5 ref.
Keywords: OVINOS; PRODUCCION ANIMAL; ALIMENTACION DE LOS ANIMALES; TRIFOLIUM SUBTERRANEUM; DIGESTIBILIDAD; SISTEMAS DE EXPLOTACION; CHILE; AGRICULTURA TECNICA